2014
DOI: 10.5296/jpag.v4i3.6127
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Human Capital and Economic Growth in MENA Countries

Abstract: The aim of this study is to analyze the relation between human capital and economic growth for the years between 1990 and 2011 in 15 MENA (Middle East and North Africa) countries. Knowles and Owen's (1995) model which is based on Mankiw et al. (1992)'s Augmented Solow Model in principle is used as the economic model in the study. However, the statistical analysis is panel-data for the countries. Human capital is represented by both health and education at the same time. The findings show that public expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous research mainly suggested three outcomes to show the way that health affects growth, i.e., positive relationship (9-16), negative relationship (1,17,18), and neutrality (19)(20)(21). On the other hand, certain studies analyze the relationship by pool (panel) data, and the results are mixed depending on different groups of economic development (1,3,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research mainly suggested three outcomes to show the way that health affects growth, i.e., positive relationship (9-16), negative relationship (1,17,18), and neutrality (19)(20)(21). On the other hand, certain studies analyze the relationship by pool (panel) data, and the results are mixed depending on different groups of economic development (1,3,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%